2008
DOI: 10.1248/jhs.54.335
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Manganese and Nickel Exposure from Beverages in Nigeria: A Public Health Concern?

Abstract: Iron, manganese and nickel were analyzed using Atomic Absorption Spectrophotometry (AAS) in 50 beverages sold in Nigeria. Iron levels ranged from 0.020-2.460 mg/l for canned and 0.020-2.090 mg/l for non-canned beverages. In 95.24% of the canned beverages, iron levels exceeded the maximum contaminant level (MCL) of 0.30 mg/l, while 75.86% of the non-canned beverages had iron levels exceeding the MCL. Manganese levels ranged from 0.001-0.730 mg/l for canned and 0.001-0.209 mg/l for noncanned beverages. 42.86% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“…Epigenetic mechanisms are influenced by heavy metal exposure [30], the latter often being a consequence of geographic location. Individuals from Nigeria, the country of origin for YRI, are more exposed to heavy metals than Europeans and Americans [31,32]. Cells, from which DNA was extracted for the CAU population, was immortalised 6-32 years before YRI cells (personal communication with Coriell).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms are influenced by heavy metal exposure [30], the latter often being a consequence of geographic location. Individuals from Nigeria, the country of origin for YRI, are more exposed to heavy metals than Europeans and Americans [31,32]. Cells, from which DNA was extracted for the CAU population, was immortalised 6-32 years before YRI cells (personal communication with Coriell).…”
Section: Discussionmentioning
confidence: 99%
“…Maduabuchi et al [9] reported that among 21 canned and 30 non-canned beverages, 95.25% and 75.86%, respectively (iron), 42.86% and 51.72%, respectively (manganese), 80.95% and 72.41%, respectively (nickel) have high concentration, while Magomya et al [10] reported that out of 24 soft drinks, 53.33%, 7.14%, 20.83%, 29.17%, and 16.67% exceeded the set safe limits for iron, copper, chromium, lead, and cadmium, respectively. Though some heavy metals could be beneficial, these metals possess deleterious effect when present or their levels in food and drinks exceed the tolerable limit [11].…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, as bebidas alcoólicas comerciais podem ser veículos de elementos tóxicos, incluindo Ni, em teor superior ao máximo aceitável. 16 A cachaça, bebida destilada nacional produzida por fermentação da cana-de-açúcar, deve atender à legislação brasileira no que tange à presença dos contaminantes inorgânicos Cu, Pb e As, limitados a 5,0; 0,2 e 0,1 mg/L, respectivamente, 17 tendo sido constatado extrapolação nos teores destes elementos em cachaças vendidas em Araraquara (SP). 18 Estudo com cachaça, terceira maior bebida alcoólica destilada mais comercializada no mundo, 19 não constatou relação entre o perfil iônico e a procedência da bebida.…”
Section: Introductionunclassified